How Do the Unemployed Search for a Job? – Evidence from the EU Labour Force Survey - Ronald Bachmann; Daniel Baumgarten (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
Using harmonized micro data, this paper investigates the job search methods of the unemployed in Europe. The analysis focuses on the importance of individual and household characteristics in this context, as well as on cross-country differences in Europe. Our findings suggest that both individual and household characteristics play an important role, with the latter being more decisive for women. However, even when controlling for these factors, remarkable differences remain between countries, which are associated with institutional characteristics at the country level. – – Auf Basis von harmonisierten Mikrodaten wird in diesem Papier das Job-Suchverhalten von Arbeitslosen in Europa untersucht. Dabei richtet sich das Augenmerk sowohl auf individuelle und haushaltsspezifische Determinanten des Suchverhaltens als auch auf Unterschiede zwischen den Ländern. Unsere Ergebnisse zeigen, dass sowohl individuelle als auch haushaltsspezifische Charakteristika - letztere vor allem bei Frauen - eine wichtige Rolle spielen. Jedoch bestehen, selbst wenn man für diese Faktoren kontrolliert, erhebliche Unterschiede zwischen den Ländern, die mit institutionellen Charakteristika des Arbeitsmarktes im Zusammenhang stehen.
Keywords: J20; J64; C38; 330; Job search; search channels